Effect of Dietary Supplementation of Giloy (Tinospora cordifolia) and Ascorbic Acid along with Different Bedding Materials on Egg Production of Japanese Quail - Poonia, Narender Kumar; Choudhary, Garima; Kumar, Vijay (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study investigated the effects of giloy (Tinospora cordifolia) and ascorbic acid supplementation along with different bedding materials  (sand B1, saw dust B2 and wheat straw B3) on egg production status of Japanese quails. Total 432 chicks (7 day-old) of Japanese quails  were divided into three equal groups (144 each) for different bedding material used and each group was further subdivided into four  groups (each of 36 chicks) on the basis of dietary treatment (control T0, giloy T1, ascorbic acid T2 and combination of both T3). Thus birds  were randomly and uniformly distributed in total 12 treatment groups comprising of 36 birds in each group and each group was further  divided into two replicates comprising 18 birds in each. Quails were fed a basal diet (control, T0) and the basal diet supplemented with  giloy 5 g/kg of diet, ascorbic acid 240 mg/kg diet and a combination of giloy 5 g/kg and ascorbic acid 240 mg/kg diet in dietary treatment  groups T1, T2 and T3, respectively. Highly significant (p
Keywords: Ascorbic acid; Giloy; Japanese quail; Total number of eggs produced per bird; Total number of eggs produced per flock